Extreme Explosions Supernovae, Hypernovae, Magnetars, and Other Unusual Cosmic Blasts - Stevenson, David S. (Astronomers' Universe, 2014)
What happens at the end of the life of massive stars? At one time we thought all these stars followed similar evolutionary paths. However, new discoveries have shown that things are not quite that simple.   This book focuses on the extreme -the most intense, brilliant and peculiar- of astronomical explosions. It features highly significant observational finds that push the frontiers of astronomy and astrophysics, particularly as before these objects were only predicted in theory.   This book is for those who want the latest information and ideas about the most dramatic and unusual explosions detected by current supernova searches. It examines and explains cataclysmic and unusual events in stellar astrophysics and presents them in a non-mathematical but highly detailed way that non-professionals can understand and enjoy.